Nucleotide Frequency Variation Across Human Genes - Louie, Elizabeth (Cold Spring Harbor Laboratory Press, 2003)
The frequencies of individual nucleotides exhibit significant fluctuations across eukaryotic genes. In this paper, we investigate nucleotide variation across an averaged representation of all known human genes. Such a representation allows us to average out random fluctuations that constitute noise and uncover remarkable systematic trends in nucleotide distributions, particularly near boundaries between genetic elements—the promoter, exons, and introns. We propose that such variations result from differential mutational pressures and from the presence of specific regulatory motifs, such as transcription and splicing factor binding sites. Specifically, we observe significant GC and TA biases (excess of G over C and T over A) in noncoding regions of genes. Such biases are most probably caused by transcription-coupled mismatch repair, an effect that has recently been detected in mammalian genes. Subsequently, we examine the distribution of all hexanucleotides and identify motifs that are overrepresented within regulatory regions. By clustering and aligning such sequences, we recognize families of putative regulatory elements involved in exonic and intronic splicing control, and 3′ mRNA processing. Some of our motifs have been identified in prior theoretical and experimental studies, thus validating our approach, but we detect several novel sequences that we propose as candidates for future functional assays and mutation screens for genetic disorders.